Education Accountability Profile in terms of Quality School Learning in the Era 4.0 - Lesmana, Gusman; Tanjung, Bahdin Nur (Indonesian Journal Education, 2022)
This article aims to describe the condition of educational accountability in terms of the quality of post-pandemic learning where this greatly influences the condition of competency development activities in schools due to the many activity restrictions imposed during the pandemic crisis. This research method is a literature review with the addition of a data survey method to representative schools in the city of Medan as a concrete manifestation of conditions in the field related to educational accountability. The findings obtained in this study are the urgency of educational accountability that needs to be improved, starting from the formal school level education level by improving the quality of learning and teaching carried out by teachers to prioritize competency development over other activities which are sometimes not too important to be carried out in schools.